Pengembangan Inventori Adaptabilitas Karier Siswa Sekolah Menengah Atas Negeri - Karina Anwar; Arbin Janu Setiyowati; Indriyana Rachmawati; Karina Anwar; Arbin Janu Setiyowati; Indriyana Rachmawati (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The purpose of this research is to produce an inventory of career adaptability of students at SMAN 8 Malang. The research model used is the ADDIE (Analysis-Design-Development-Implementation-Evaluation) development model. The research subjects consisted of 400 students of class XI and XII of SMAN 8 Malang. The instruments used in this study were the material expert test assessment instrument and the linguist test instrument. The data analysis technique from the material and language expert test is quantitative and qualitative. The results of the analysis from material experts and linguists there are several items that need to be improved so that they can produce a decent product. The instrument trial was carried out in two stages. Testing data analysis using the Rasch model through Winsteps software. The results of data analysis showed that the instrument met the unidimensionality requirements. The results of the rating scale analysis show that the use of a four-level scale is appropriate. In general, it can be concluded that the career adaptability inventory has good psychometric attributes so that it can be used to measure the career adaptability level of SMAN 8 Malang students. Abstrak: Penelitian bertujuan menghasilkan inventori adaptabilitas karier siswa SMAN 8 Malang. Model penelitian yang digunakan adalah model pengembangan ADDIE (Analysis-Design-Development-Implementation-Evaluation). Subjek penelitian terdiri atas 400 siswa kelas XI dan XII SMAN 8 Malang. Penggunaan instrumen dalam penelitian ini adalah instrumen penilaian uji ahli materi dan instrumen uji ahli bahasa. Teknik analisis data dari uji ahli materi dan bahasa adalah kuantitatif dan kualitatif. Hasil analisis dari ahli materi dan ahli bahasa terdapat beberapa item yang perlu diperbaiki sehingga dapat menghasilkan produk yang layak. Uji coba instrumen dilakukan melalui dua tahap. Teknik analisis data menggunakan model Rasch melalui perangkat lunak Winsteps. Hasil analisis data menunjukkan bahwa instrumen memenuhi syarat unidimensionalitas. Hasil analisis rating scale menunjukkan bahwa penggunaan skala empat tingkat sudah sesuai. Secara umum dapat disimpulkan bahwa inventori adaptabilitas karier ini mempunyai atribut psikometris yang baik sehingga inventori ini dapat digunakan untuk mengukur tingkat adaptabilitas karier siswa SMAN 8 Malang.